The Relationship between Serum Level of High-Sensitivity C-Reactive Protein (hs-CRP) and Residual Renal Function in Patients under Peritoneal Dialysis during One Year - Shiva Seirafian; Mojgan Mortazavi; Azadeh Falahatkar (مجله دانشکده پزشکی اصفهان, 2018)
Background: Residual renal function helps the part of solute clearance in patients under peritoneal dialysis. Some studies showed that decline in renal function maybe associate with production of inflammatory mediators in these patients. The aim of this study was to assess the relationship between serum level of high-sensitive C-reactive protein (hs-CRP) and residual renal function in patients under peritoneal dialysis during one year.